Artisanal fish farming and youth employability in Côte d’Ivoire - YE, Sata; KOUTOU, N’Guessan Claude; TANOH, Hilaire (IJRDO - Journal of Social Science and Humanities Research, 2020)
Analysis of youth employability on the labor market in Côte d’Ivoire is a very complex phenomenon because it is influenced by the diversity factors that determine its evolution. The youth employability is a challenge for the national and international community. It is about the problem of efficient use of human resources for the construction of sustainable development. This study highlights artisanal fish farming as a sector that leads to decent youth employment in Côte d’Ivoire. The results revealed that more than half of the surveyed lands were inherited (54.63%). These farms (81.82%) have regular access to water, which facilitates the implementation of fish farming activities. About 69.49% of farms have their source of water coming from the groundwater. Small scale farms are the most dominant (45.57%). In terms of access to inputs, 63.21% of farms produce their fry and 64.08% make their own food. The study shows that fish farming is an important development sector and therefore constitute an interesting alternative to youth employability in Côte d’Ivoire.